Implementasi Akad Murbahah pada Koperasi Syariah : Studi Kasus Koperasi Pegawai Negri Syariah RSUD Prof. Dr. MA Hanafiah SM. Batusangkar - Fauza Dwi Zetria (Journal of Islamic and South East Asian Finance and Accounting, 2024)
This paper describes the implementation of murabaha contract at the IFI under studied (Koperasi Pegawai Negeri Syariah RSUD Prof. Dr. MA Hanafiah SM Batusangkar). This research is qualitative in nature. Data was collected through in-depth interviews with key informants and observations. The finding of this study indicated that the implementation of murabaha contarct at the IFI under studied still contained deviations from the ideal concept: murabaha and wakala contracts, in fact, had been done parallel and the goods were not available at the time of the contract signed and the proof of trasactions with the third parties were not available. This means that the status of the goods sold were not clear. The implementation therefore had not fully followed the guidance or Fatwa issued by DSN MUI No.04/DSN-MUI/IV/2000 on murabahah.